2017
DOI: 10.1016/j.biocontrol.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life history traits of indigenous Italian parasitoids of Drosophila suzukii and their effectiveness at different temperatures

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 66 publications
5
44
0
1
Order By: Relevance
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).…”
Section: F I G U R Esupporting
confidence: 78%
See 2 more Smart Citations
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).…”
Section: F I G U R Esupporting
confidence: 78%
“…These results suggest that L. heterotoma's virulence is not strong enough to resist the immune reaction of D. suzukii. This was also observed in other studies (Chabert et al, 2012;Kacsoh & Schlenke, 2012;Knoll et al, 2017;Poyet et al, 2013;Rossi Stacconi et al, 2017).However, a single female succeeded to complete its development in this study, and higher rates of successful development were observed when testing various geographic strains of the parasitoid (P. Girod A. japonica and L. japonica that attacked and developed in larvae in both substrates, Ganaspis sp. parasitized many more larvae in blueberries compared to artificial diet.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Only one L. heterotoma progeny was able to overcome the immune response of D. suzukii and, although in some cases the rate of encapsulation avoidance may be much higher (e.g. 10–30% in Rossi-Stacconi et al 2015, 2017), parasitism by L. heterotoma has not yet been found in the field (Kenis et al 2016). However, it cannot be ruled out that over time L. heterotoma or other native larval parasitoid can become adapted to the new host, as observed in many other cases (Henter and Via 1995; Urbaneja et al 2000; Jones et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Leptopilina heterotoma Thompson (Hymenoptera, Figitidae)] that are rarely able to complete their development in D. suzukii (Chabert et al 2012; Poyet et al 2013; Gabarra et al 2015; Rossi-Stacconi et al 2015; Daane et al 2016). In Europe, only the generalist pupal parasitoids such as Trichopria drosophilae Perkins (Hymenoptera: Diapriidae) and Pachycrepoideus vindemmiae Rondani (Hymenoptera: Pteromalidae) can successfully develop in D. suzukii and T. drosophilae is considered for augmentative biocontrol, but its efficacy to control D. suzukii populations in infested orchards remains to be shown (Knoll et al 2017; Rossi-Stacconi et al 2017). Compared to chemical control, classical biological control, when applied properly, is often less harmful to the environment, shows direct benefits for food safety and provides effective long-term control of invasive species.…”
Section: Introductionmentioning
confidence: 99%